RANCANG DESAIN TIANG LAMPU JALAN YANG INOVATIF - Nada Ikbar Hafizhoh; Muhamad Zainudin; Gilang Rusadi Ahmad (Yayasan Nusantara Hasana Berdikari, 2023)
Street light is a facility provided as a street light, which is very much needed as a road light and navigation for motorists. The development of these street lights has been very diverse, both from design to power generation used, but not all of them are uniform in use because they still use conventional street lights. answer the needs of the facilities used and produce innovative street lights. The results obtained from observations and questionnaires from respondents indicate that there are still many street lamps that are matched and the materials used are not sturdy. In this regard, the design of this innovative street light has several features, namely, LED lights, a lower ring ring feature, an upper ring ring feature, a solar panel, with a height of 300 cm, a bottom diameter of 8.5 cm, an upper diameter of 4.3 cm. And it is equipped with coloring on the lamp posts which is simple, attractive, practical, and increases rider comfort.